2014
DOI: 10.1186/1471-2474-15-384
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reoperations due to infection in the Swedish Hip Arthroplasty Register

Abstract: BackgroundComplete or almost complete recording of reoperations is essential to enable a correct interpretation of data in arthroplasty registers. The completeness of recordings due to infection is unknown in the Swedish Hip Arthroplasty Register (SHAR). We therefore used a combination of data from the Swedish Prescribed Drug Register (SPDR) and studies of medical records to validate the data of reoperations due to infection in the SHAR.MethodsAll patients registered for a primary Total Hip Replacement (THR) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 15 publications
(15 reference statements)
2
62
0
Order By: Relevance
“…However, such registries lack clinical and radiologic data, making accurate analysis of revision indications difficult. Additionally, some studies show registry capture of certain revision indications is poor [12,28]. In the current study, we combined local hospital data with national joint registry data to provide more-complete followup of patients who have undergone TKA during a long period and to allow accurate clinical and radiographic analyses of these indications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such registries lack clinical and radiologic data, making accurate analysis of revision indications difficult. Additionally, some studies show registry capture of certain revision indications is poor [12,28]. In the current study, we combined local hospital data with national joint registry data to provide more-complete followup of patients who have undergone TKA during a long period and to allow accurate clinical and radiographic analyses of these indications.…”
Section: Discussionmentioning
confidence: 99%
“…National joint registries from Australia, United Kingdom, Sweden, and New Zealand all show aseptic loosening to be the most-common failure mechanism after primary TKA but capture of revision surgery resulting from infection often is poor [10,15,23,28]. Lindgren et al [12] reported a capture rate of 67% by the Swedish Hip Arthroplasty Register for reoperation resulting from PJI after THA. Zhu et al [28] reported the New Zealand Joint Registry was 63% accurate in detecting reoperations for PJI (in hip and knee arthroplasties) when compared with data from the International Classification of Diseases, 9th and 10th editions, revision codes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the national arthroplasty register studies on the incidence of PJI included data from microbiology databases. Furthermore, relying solely on national arthroplasty registers in the analysis of PJI trends may be questionable because studies have shown that these registers underestimate the incidence of PJI by up to 40% 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Periprosthetic infection occurs in 0.22% to 3% of patients who undergo arthroplasty [3,4,8,9,15,21], and it is always devastating. Several techniques have been applied in an attempt to completely eradicate infection [14].…”
Section: Introductionmentioning
confidence: 99%